The Influence of Independence, Competence and Time Budget Pressure on Audit Quality with Auditor Ethics as a Moderating Variable at Big Ten Public Accounting Firms - Fajar Mardika (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2024)
This study aims to determine "the influence of independence, competence and time budget pressure on audit quality with auditor ethics as a moderating variable". The method in this research is quantitative with primary data sources. The population in this study are auditors who work at Public Accounting Firms in the DKI Jakarta area who are members of the Big Ten and are registered as IAPI members. Sampling was carried out using probability sampling so that the minimum sample used in this research was 83 respondents. The data analysis used in the research is SEM PLS data analysis version 4.0 Based on the results of research using hypothesis testing, it shows that Independence, Competence and Time Budget Pressure have a significant effect on Audit Quality. Auditor Ethics are able to moderate Independence, Competence and Time Budget Pressure.